Indonesian Pre-service Teacher Journey in International Teaching Practicum - Barlaman, Moh. Aang Fajar; Umamah, Atik (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
The increasing importance of cross-cultural competence in education has made international teaching practicum (ITP) programs essential for pre-service teachers. These programs provide unique opportunities to enhance pedagogical skills and develop global awareness, particularly for English as a Foreign Language (EFL) teachers in diverse cultural contexts. However, the specific experiences of Indonesian pre-service teachers participating in ITP programs remain underexplored. This study aims to explore the experiences of Indonesian pre-service English teachers during an ITP program in Malaysia, focusing on the journey, personal growth, and professional development achieved throughout the program. Using a qualitative narrative inquiry approach, this exploratory case study examined the experiences of one Pre-service teacher from the English Education Department, referred to as